Procoagulant and inflammatory response of virus-infected monocytes - Bouwman, J. J. M.; Visseren, F. L. J.; Bosch, M. C.; Bouter, K. P.; Diepersloot, R. J. A. (European journal of clinical investigation, 2002)
Background Monocytes play a prominent role in inflammation, coagulation and atherosclerosis by their ability to produce tissue factor (TF) and cytokines. The aim of the present study was to establish whether virus‐infected monocytes initiate coagulation. In addition, the production of cytokines by monocytes may accelerate the chronic process of atherosclerosis and may contribute to coronary syndromes by eliciting plaque instability. Materials and methods Monocytes were isolated by Vacutainer®, BD Biosciences, Alphen aan den Rijn, Netherlands and subsequent magnetic cell sorting (MACS®, Milteny Biotec, Bergish Gladbach, Germany). Coagulation times in normal pooled plasma and Factor VII‐deficient plasma were measured after infection with cytomegalovirus (CMV), Chlamydia pneumoniae (Cp) and influenza A\H1N1. Anti‐TF antibodies were added to neutralize TF expressed on monocytes. Interleukins (IL) 6, 8 and 10 were measured in the supernatants. Results Chlamydia pneumoniae‐ and CMV‐infected monocytes decreased the clotting time by 60%, and influenza‐infected monocytes by 19%, as compared to uninfected monocytes. Procoagulant activity was absent when Factor VII‐deficient plasma or anti‐TF antibodies were used. Monocytes produced both IL‐6 and IL‐8 after infection with CMV (317 pg mL−1 and 250 pg mL−1) or Cp (733 pg mL−1 and 268 pg mL−1). Similar results were obtained for influenza virus‐infected monocytes, but the levels of both cytokines were 3–5‐fold higher (1797 pg mL−1 and 725 pg mL−1). Interleukin‐10 was not produced by infected monocytes. Conclusion The procoagulant activity of virus‐infected monocytes is TF‐dependent. Although influenza infection did not generate a significant reduction in clotting time, the pronounced expression of IL‐6 and IL‐8 may induce local and/or systemic inflammatory reactions, which may be associated with plaque rupture and atherosclerosis. The lack of production of the anti‐inflammatory cytokine IL‐10 may even accelerate these processes.